Narrative Historiography and the Aesthetics of Desire in Jeanette Winterson’s Fiction - Sharma, Khum Prasad (Mindscape: A Journal of English & Cultural Studies, 2025)
Jeanette Winterson’s fiction has a special place in contemporary British literature. Her novels combine creative storytelling with deep reflections on history, love, and identity. She does not follow traditional realism. Instead, she experiments with narrative forms while exploring desire and passion. This article examines The Passion (1987) and Sexing the Cherry (1989). It focuses on how Winterson rewrites history and reimagines erotic subjectivity. The study uses Linda Hutcheon’s theory of historiographic metafiction and Luce Irigaray’s feminist ideas on desire. Hutcheon explains how Winterson questions historical authority through fictionalized personal narratives. This shows that history is fragile and subjective. Irigaray’s ideas help analyze how Winterson presents gender and sexuality. In Sexing the Cherry, her characters challenge traditional gender roles and express desire as open, creative, and transformative. The findings show that Winterson blends metafictional techniques with lyrical explorations of passion. In The Passion, she mixes Napoleon-era history with imagination, offering new perspectives on the past. In Sexing the Cherry, she destabilizes gender norms and portrays desire as fluid. These novels highlight her originality in narrative style and themes. This study demonstrates Winterson’s contribution to postmodern literature and feminist thought. Her work shows how rewriting history and exploring desire can challenge cultural norms and offer new ways of thinking about identity, love, and human experience.